An Unusual Extremely Distant Noncommunicating Uterine Horn with Myoma and Adenomyosis Treated with Laparoscopic Hemihysterectomy - Michele Morelli; Roberta Venturella; Rita Mocciaro; Daniela Lico; Fulvio Zullo (Hindawi Limited, 2013)
A 41-year-old woman referred to us with dysmenorrhea and severe pelvic pain although she was previously submitted to right laparotomic adnexectomy for ovarian endometrioma and to a subsequent operative laparoscopy for pelvic adhesions. After ultrasound examination, the patient underwent diagnostic hysteroscopy and operative laparoscopy which confirmed the clinic suspect of an unicornuate uterus. However, it was very unusual to see an extremely distanced right horn, without communication with uterus, without adnexa, and with a small myoma belonging to it. Moreover, omentum and bowel were attached to fundus of right horn and thick adhesions fixed it to rectum and right pelvic wall. Therefore, identification of anatomical structures was difficult, as it was extremely arduous to isolate the ureter, which was involved inside the adhesions surrounding the right uterine horn. Nevertheless, laparoscopic right hemihysterectomy was successfully performed and right horn was sent to our pathologist who recognized hypotrophic endometrium and adenomyosis.